Effectiveness of Early Childhood Education Tutors’ Teaching Skills Implemented by Cooking Demonstration Videos about Healthy Food - Riska, Nur (Universitas Negeri Semarang, 2018)
This research is aimed at analyzing an effectiveness of Early Childhood Education tutors’ teaching skills implemented by cooking demonstration videos about healthy food. This research conducted at Preschool in Jakarta. A research design used was Quasi-Experimental Design. Data analysis techniques used were t-test by using SPSS 16 version. Based on the result, it revealed that p-value is 0.001 <α (0.05) so, there is a significant influence on the average of Early Childhood Education tutors’ teaching skills after implemented cooking demonstration videos about healthy food. An increasing value is 0.632 in the range of 0.7> (N-gain) ≥ 0.3 so, the skill improvement is in the medium category. An effectiveness description after implemented healthy cooking video shows the average percentage value is 91%. It indicates very effective criteria.